Electronic commerce benefits and adoption barriers in small and medium enterprises in Gweru, Zimbabwe - Dube, Thulani; Chitura, Tofara; Runyowa, Langton (Journal of Internet Banking and Commerce, 2021)
This paper reports on the findings of an exploratory survey research whose main purpose was to explore electronic commerce benefits and adoption barriers in small and medium enterprises (SMEs) in Gweru, Zimbabwe. Using an exploratory research design, a structured survey instrument was developed and administered to thirty SMEs conveniently selected from a database of SMEs in Gweru. The study found that though SMEs in Gweru appear to have adopted electronic commerce related technologies, the usage level of these technologies is still in its infancy, while the predominant use of electronic commerce applications was for communication/informative purposes. Perceptions and attitudes of SMEs towards electronic commerce and its relayed technologies were strongly favourable. The most significant benefits derived from electronic commerce adoption and usage were improved quality of information and communicating with suppliers and customers. Regarding barriers, the technology was deemed too expensive and incompatible with the way SMEs/customers do business. The study concludes that in order to reap significant benefits from electronic commerce, survey SMEs need to adopt sophisticated e-commerce technologies.